Reference interest rate, monetary aggregates and economic cycles - Rivas Santos, Pablo Hermenegildo (2018)
This article qualitatively and quantitatively analyzes the effects of the control of the reference interest rate and of the monetary aggregates (by the Central Reserve Bank) on the productive structure and the processes of coordination and economic interaction of society. It is verified quantitatively that the relation low interest rate of reference-high level of monetary aggregates and Cyclical Behavior of the Gross Domestic Product defines the phases of recovery and boom of the productive sectors more intensive in time and capital; and the phases of slowdown and recession of these productive sectors. Clasificación JEL: E. Macroeconomics and Monetary Economics, E 52 Monetary Policy.